PENGARUH DUE PROFESSIONAL CARE, INDEPENDENSI, PENGALAMAN AUDITOR DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT DENGAN LOCUS OF CONTROL INTERNAL SEBAGAI VARIABEL MODERASI - Yuhan, Elvira (Ma Chung Press, 2022)
The purpose of this study was to examine the effect of due professional care, independence, experience, and competence on audit quality in Malang City moderated by locus of control. the number of respondents used in this study were 40 people from 11 public accounting firms. This study uses Moderated Regression Analysis as a test tool. The results of this study indicate that due professional care has a positive effect on audit quality on auditors in Malang City. while independence, experience, and expertise have no effect on investor decision making in Malang City. Locus of control moderating variable did not strengthen the influence of all research variables, namely due professional care, independence, experience, and competence on audit quality. This study shows that there are several variables that do not affect audit quality, which can be caused by many auditors adhering to principles that are in accordance with applicable regulations. Each region has different characteristics, educational background also has a role in influencing individual characteristics in decision making, because each individual has a variety and different levels of education depending on the individual's ability to interpret the knowledge obtained.